Huygens and Fontenelle on Aliens and Humans - Špelda, Daniel (Teorie vědy / Theory of Science, 2018)
The article deals with selected aspects of two well-known publications on the multiplicity of worlds and extraterrestrial life that emerged at the end of the 17th century. These are Entretiens sur la pluralité des mondes (1686) by Bernard de Fontenelle and Cosmotheoros (1698) by Christiaan Huygens. In the first part, the article focuses primarily on how both authors understand the position of man in an inhabited and unbounded universe. Fontenelle and Huygens provide in their texts a convincing refutation of the often repeated notion that the idea of the infinite universe awakened terror and fears in early modern intellectuals. Actually, for them, the unbounded universe meant a celebration of reason that is able to emancipate itself from a geocentric superstition and anthropocentrism. At the same time, in the spirit of the early Enlightenment, it was also a celebration of the cosmic universality of reason. In its second part, the article deals with so-called cognitive passions: especially with fear, amazement and curiosity. The analysis of Huygens’ and Fontenelles’ works confirms and deepens some points of Lorraine Daston’s research. It turns out that at the end of the 17th century, fear and admiration were clearly understood as manifestations of ignorance and backwardness, although in the previous philosophical tradition they were associated with piety and the beginning of philosophy. Compared to it, traditionally condemned curiosity has become a legitimate, even desirable, characteristics of a true scientist.